Comparison of De Novo Cancer Incidence in Australian Liver, Heart and Lung Transplant Recipients. Issue 1 (24th October 2012) - Na, R.; Grulich, A. E.; Meagher, N. S.; McCaughan, G. W.; Keogh, A. M.; Vajdic, C. M.
<x xml:space="preserve">Abstract</x> Population‐based evidence on the relative risk of de novo cancer in liver and cardiothoracic transplant recipients is limited. A cohort study was conducted in Australia using population‐based liver (n = 1926) and cardiothoracic (n = 2718) registries (1984–2006). Standardized incidence ratios (SIRs) were computed by cancer type, transplanted organ and recipient age. Cox regression models were used to compare cancer incidence by transplanted organ. During a median 5‐year follow‐up, the risk of any cancer in liver and cardiothoracic recipients was significantly elevated compared to the general population (n = 499; SIR = 2.62, 95%CI 2.40–2.86). An excess risk was observed for 16 cancer types, predominantly cancers with a viral etiology. The pattern of risk by cancer type was broadly similar for heart, lung and liver recipients, except for Merkel cell carcinoma (cardiothoracic only). Seventeen cancers (10 non‐Hodgkin lymphomas), were observed in 415 pediatric recipients (SIR = 23.8, 95%CI 13.8–38.0). The adjusted hazard ratio for any cancer in all recipients was higher in heart compared to liver (1.29, 95%CI 1.03–1.63) and lung compared to liver (1.65, 95%CI 1.26–2.16). Understanding the factors responsible for the higher cancer incidence in cardiothoracic compared to liver recipients has the potential to lead to targeted cancer prevention strategies in this high‐risk population.